2008
DOI: 10.1016/j.jedc.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Can consumption spillovers be a source of equilibrium indeterminacy?

Abstract: In this paper, we show that consumption externalities are a source of equilibrium indeterminacy in a growth model with endogenous labor supply. In particular, when the marginal rate of substitution (MRS) between an agent's own consumption and the others' consumption is constant along the equilibrium path, the equilibrium does not exhibit indeterminacy. In contrast, when that MRS is not constant, the equilibrium may exhibit indeterminacy even if the elasticity of the labor demand is smaller than the elasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 12 publications
1
34
2
Order By: Relevance
“…However, unlike this study, which includes jealousy and admiration, their indeterminacy arises only in altruistic catching-up-with-theJoneses preferences. In contrast to exogenous labor supply in this article, indeterminacy in Alonso-Carrera, Cabellé, and Raurich (2008) and Chen et al (2010) required endogenous labor supply and habit stocks with a large adjustment coefficient for current consumption (see the excellent survey in Benhabib & Farmer, 1999). In an endogenous growth model with external habits and implementation-efficient tax policies, not only showed the unique balanced growth path in conjunction with the saddle stability of the transitional path, but also recognized the possibility of multiple optimum tax rates, which may suggest the existence of multiplicity in the case of a second-best social optimal allocation that I consider.…”
Section: Introductionmentioning
confidence: 92%
“…However, unlike this study, which includes jealousy and admiration, their indeterminacy arises only in altruistic catching-up-with-theJoneses preferences. In contrast to exogenous labor supply in this article, indeterminacy in Alonso-Carrera, Cabellé, and Raurich (2008) and Chen et al (2010) required endogenous labor supply and habit stocks with a large adjustment coefficient for current consumption (see the excellent survey in Benhabib & Farmer, 1999). In an endogenous growth model with external habits and implementation-efficient tax policies, not only showed the unique balanced growth path in conjunction with the saddle stability of the transitional path, but also recognized the possibility of multiple optimum tax rates, which may suggest the existence of multiplicity in the case of a second-best social optimal allocation that I consider.…”
Section: Introductionmentioning
confidence: 92%
“…Several papers have been studying the effects of certain specific market distortions (linked to externalities, imperfectly competitive markets, or government intervention) on local dynamics, 1 but a systematic analysis within a general unified framework, able to compare the importance of different types of distortions as a route to indeterminacy and bifurcations, is still missing. In order to do that we introduce a general framework, able to account for market distortions without specifying a priori their source, and highlight the main channels through which indeterminacy occurs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that consumption externalities do not generate indeterminacy of the equilibrium path (1) when the labor supply is exogenous (Liu and Turnovsky, 2005); or (2) when the utility function has the restricted homotheticity (RH) property 1 (Guo, 1999;Weder, 2000) even if the labor supply is endogenous. However, indeterminacy can arise when consumption externalities modify the Frisch labor supply, which requires that the utility function is nonseparable between consumption and leisure (Alonso-Carrera, Caballe, and Raurich, 2008).…”
Section: Introductionmentioning
confidence: 99%